What you are looking for is in the library : a novel - Aoyama, Michiko, 1970- (Hanover Square Press, 2023)
What are you looking for? So asks Tokyo's most enigmatic librarian. For Sayuri Komachi is able to sense exactly what each visitor to her library is searching for and provide just the book recommendation to help them find it. A restless retail assistant looks to gain new skills, a mother tries to overcome demotion at work after maternity leave, a conscientious accountant yearns to open an antique store, a recently retired salaryman searches for newfound purpose. In Komachi's unique book recommendations they will find just what they need to achieve their dreams. What You Are Looking For Is in the Library is about the magic of libraries and the discovery of connection. This inspirational tale shows how, by listening to our hearts, seizing opportunity and reaching out, we too can fulfill our lifelong dreams. Which book will you recommend?"--